PEX16: a multifaceted regulator of peroxisome biogenesis - Kim, Peter; Mullen, Robert (Frontiers in Physiology, 2013)
Peroxisomes are formed by two distinct pathways: the growth and fission of mature peroxisomes and de novo synthesis at the endoplasmic reticulum (ER). While many of the molecular mechanisms underlying these two pathways remain to be elucidated, it is generally accepted that their relative contribution to peroxisome formation may vary depending on the species, cell type and/or physiological status of the organism. One pertinent example of the apparent differences in the regulation of peroxisome biogenesis among evolutionarily diverse species is the involvement of the peroxin PEX16. In Yarrowia lipolytica, for instance, PEX16 is an intraperoxisomal peripheral membrane protein that participates in peroxisomal fission. By contrast, Human PEX16 is an integral membrane protein that is thought to function at the ER during the early stages of de novo peroxisome formation and also recruits peroxisomal membrane proteins directly to mature peroxisomes. Similarly, PEX16 in the plant Arabidopsis thaliana is speculated to be a PMP receptor at the ER and peroxisomes, and is also required for the formation of other ER-derived organelles, such as oil and protein bodies. Here we briefly review the current knowledge of Y. lipolytica, human and A. thaliana PEX16 in the context of our overall understanding of peroxisome biogenesis and the role of the ER in this process in these three divergent species.